Truth-claim shift: philosophical studies on former terrorism inmate in Indonesia - Waston, Waston; Hassan, Aminudin (Human Resource Management Academic Research Society, 2019)
This study explores a gradual shift of thought on truth claim hold by former terrorist inmates (known in Indonesia as ex-napiter). Itis based on data interviews with three ex-napiter, namely, Yusuf, a former jihadist in Southeast Asia who was accused of storing explosives and planning a bombing at Sri Rejeki brothel in Semarang; Wawan, who was charged due to his involvement in Bali Bombing 2 and hiding terrorist kingpin; and Mamo, a former member of Negara Islam Indonesia (Indonesian Islamic State) and an expert on assembling firearms. The study shows that the ex-napiter gradually changed their perspective on truth claim in four stages.First is the conflict period, where they cannot accept other truths except their own. Second is the independent period, which occurs when they have been caught by the police but have not yet accepted another truth. Third is the process of change, which produces dialogue about truths and raises the possibility of accepting other truths. Forth is the integration stage, where ex-napiter have discovered new truths and be able to hold their own belief without necessarily rejecting the truth hold by the state. This study is expected to shed some lights on the perspectives of terrorist prisoners and former prisoners in Indonesia.